A new approach to the treatment of advanced heart failure: a case report. Issue 2 (12th January 2021) - Robles-Mezcua, Ainhoa; Villaescusa-Catalán, José Manuel; Melero-Tejedor, José María; García-Pinilla, José Manuel
Abstract: Background: Autonomic imbalance characterized by sympathetic predominance and decreased parasympathetic transmission is a classic feature of heart failure (HF) with reduced left ventricular ejection fraction, leading to disease progression, exercise intolerance, ventricular remodelling, arrhythmias, and premature death. The underlying mechanisms to these processes are not yet fully understood, but the current treatments influence this dysregulation, towards an inhibition of sympathetic hyperactivation. New therapies, such as the stimulation of carotid baroreceptors, enhance this inhibition to restore autonomic balance and to be able to cope with these mechanisms. Case summary: We report the case of a 76-year-old male with advanced HF at an advanced stage, refractory to optimal treatment, and included in a programme of ambulatory infusions of Levosimendan as compassionate treatment. The patient presented with multiple episodes of decompensated HF secondary to ventricular arrhythmias. A multidisciplinary team decided to implant a baroreceptor stimulator device (Barostim Neo) in order to improve HF symptoms and quality of life, as well as trying to decrease the burden of arrhythmias. The procedure was performed with no complications and good therapeutic response, resulting in a significant reduction of arrhythmias. Discussion: Treatment with a baroreceptor stimulating device is presented as a safe and effective option in our patients with advanced HF refractory to conventional treatment, to improve their quality of life and reduce symptoms; in addition to appearing as a promising option in those with arrhythmic events, which are difficult to control with usual treatments and procedures.